Partisipasi Remaja Dalam Pemanfaatan Pelayanan Pusat Informasi Konseling Remaja - Indah Puspitasari (STIKes Ibnu Sina Ajibarang, 2023)
Background: Adolescent problems are things that should be highlighted at this time, this is because youth is a transitional period that will cause various problems. According to the BKKBN (2012) the problems that stand out among adolescents are issues around the Adolescent Reproductive Health Triad (KRR), namely sexuality, HIV/AIDS and drugs. The results of the 2012 Indonesian Demographic Health Survey (IDHS) for Adolescent Reproductive Health (KRR) showed that 9.3% of adolescents stated that they had had premarital sex. Based on data from the National Narcotics Agency (BNN) in 2014, 27.32% of students were drug users. The low knowledge of adolescents about reproductive health is inadequate which can be seen by only 35.3% of young women and 31.2% of young men aged 15-19 years knowing that a woman can get pregnant with one sexual intercourse. Adolescents' knowledge of sexually transmitted infections (STIs) is still low where only 35% of women and 19% of men know gonorrhea, 14% of women and 4% of men know about genital herpes while other types of STIs are below 1%.